Nudging Away False News: Evidence from a Social Norms Experiment. Issue 1 (9th November 2020) - Andı, Simge; Akesson, Jesper
Abstract: Many are concerned with the proliferation of false information on social media. This article explores whether "social norm-based nudges" can help address this issue by changing the sharing behaviour of social media users. In order to do so, we conduct an online survey experiment ( n  = 1, 003), where participants are randomly exposed to a social norm-based message while choosing to read and/or share a false news article. The message warns participants that there is an abundance of "false information" online and tells them that most responsible people think twice before sharing articles with their network. Our analysis finds that the nudge reduced the proportion of people willing to share the article by 5.1 percentage points, with a 46.7% increase in the proportion of respondents stating that they do not want to share the article because it is false or inaccurate.